1998
DOI: 10.2307/44152984
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly Antisymmetric Functions With Bounded Range

Abstract: The goal of this note is to construct a uniformly antisymmetric function f : R → R with a bounded countable range. This answers Problem 1(b) of Ciesielski and Larson [6]. (See also the list of problems in Thomson [9] and Problem 2(b) from Ciesielski's survey [5].) A problem of existence of uniformly antisymmetric function f : R → R with finite range remains open.A function f : R → R is said to be uniformly antisymmetric [6] (or nowhere weakly symmetrically continuous [9]) provided for every x ∈ R the limit li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…In [2] Ciesielski proved that there is no nowhere weakly symmetrically continuous function with three-element range and in [3] he showed that the technique of [2] cannot be used to prove that there is no nowhere weakly symmetrically continuous function with four-element range. It is still an open question (see [7,Problem 1(a)], [6, Problem 2(a)], or [12]) whether there exists a nowhere weakly symmetrically continuous function with finite range, though Ciesielski and Shelah [8] constructed a nowhere weakly symmetrically continuous function with bounded countable range.…”
mentioning
confidence: 99%
“…In [2] Ciesielski proved that there is no nowhere weakly symmetrically continuous function with three-element range and in [3] he showed that the technique of [2] cannot be used to prove that there is no nowhere weakly symmetrically continuous function with four-element range. It is still an open question (see [7,Problem 1(a)], [6, Problem 2(a)], or [12]) whether there exists a nowhere weakly symmetrically continuous function with finite range, though Ciesielski and Shelah [8] constructed a nowhere weakly symmetrically continuous function with bounded countable range.…”
mentioning
confidence: 99%
“…We do not know if the same is true for 4-valued functions. Recently Ciesielski and Shelah [4] showed that there is an everywhere weakly symmetrically discontinuous function with bounded range.…”
mentioning
confidence: 99%